Forces and gravity - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2001)
Discusses forces such as air pressure, inertia, and gravity, and how they affect daily life. Includes related activities
Teacher's guide in PDF and Microsoft Word format
Windows system requirements : Windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, minimum resolution of 640 X 480, 16-bit color, 4 X CD-ROM drive
Macintosh system requirements : Power PC macintoch at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 Mb available RAM, minimum of 25 MB free had disc space, 640 X 480 resolutions, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Gravity -- Juvenile literature; Motion -- Juvenile literature; Gravity; Motion; Force and energy